HERÓIS DA NATUREZA: a construção do herói por meio do discurso ambientalista no ciberativismo do Greenpeace - Alves, Celena Pereira (2011)
This study proposes a reflection on the treatment of the imaginary hero of the campaign of non-governmental organization Greenpeace on its website. The corpus was the editorials designed to promote each of its action front: Amazon, Climate and Energy, Nuclear, Ocean and Transgenic. The amount of five editorials were collected on April 18, 2010. In the social context, this NGO is inserted into a conflict between natural resources conservation and industrial and economic development. Furthermore, a change in the paradigms and values of social relations due to technological advances, and the emergence of cyberspace. The aim therefore is to understand how the relation between of the actions of Greenpeace and the imaginary hero benefits joining the cyber activism. For that we use a discourse analysis of the French line as theoretical and methodological, axis, including as main thinkers Patrick Charaudeau and Dominique Maingueneau, whose ideas have helped to examine how language is used in these editorials, studying its context, resulting in ideological discourse pervaded by the hero s imagery. The study revealed that the discursive techniques used in the editorials helped to create the ethos of the hero, the villain and the girl and that these elements appreciate the actions of Greenpeace to a heroic level.